2019
DOI: 10.1111/pce.13567
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbonate drives local adaptation in Arabidopsis thaliana

Abstract: High soil carbonate limits crop performance especially in semiarid or arid climates. To understand how plants adapt to such soils, we explored natural variation in tolerance to soil carbonate in small local populations (demes) of Arabidopsis thaliana growing on soils differing in carbonate content. Reciprocal field-based transplants on soils with elevated carbonate (+C) and without carbonate (−C) over several years revealed that demes native to (+C) soils showed higher fitness than those native to (−C) soils w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 70 publications
3
66
1
Order By: Relevance
“…However, dicots like peas, beans, or sunflowers suffer more intense root growth inhibition due to CO 2 and/or HCO 3 − than the monocots barley and oats [ 123 ]. Recently soil carbonate has been identified as a main selection factor that drives local adaptation in natural populations of A. thaliana , which is a calcifuge species able to colonize soils with moderate carbonate contents [ 188 ].…”
Section: Plant Response To Bicarbonate-rich Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dicots like peas, beans, or sunflowers suffer more intense root growth inhibition due to CO 2 and/or HCO 3 − than the monocots barley and oats [ 123 ]. Recently soil carbonate has been identified as a main selection factor that drives local adaptation in natural populations of A. thaliana , which is a calcifuge species able to colonize soils with moderate carbonate contents [ 188 ].…”
Section: Plant Response To Bicarbonate-rich Soilsmentioning
confidence: 99%
“…Induction of root accumulation and exudation of coumarin-type phenolics with high affinity for Fe has been reported as a response to Fe-deficiency under high pH conditions in A. thaliana [ 198 ]. An A. thaliana population which is naturally adapted to moderate soil carbonate had higher rates of coumarin root exudation than a sensitive population [ 188 ]. Furthermore, prevention of the imbalance of organic acid concentrations caused by dark fixation of HCO 3 − and shifting of C org into the shikimate pathway for the production of phenolic compounds has been reported as a mechanism of the extreme HCO 3 − tolerance in Parietaria difusa [ 199 ].…”
Section: Plant Response To Bicarbonate-rich Soilsmentioning
confidence: 99%
“…In previous studies, we identified two contrasting demes of A. thaliana with differential tolerance to moderate soil alkalinity: the sensitive population T6 (c−) and the tolerant A1 (c+) [ 23 ]. A1 (c+) is native to areas near to calcareous soils, and soil CaCO 3 content and pH in its habitat are higher than in native soils of T6 (c−) , which are derived from silica parental rock ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we identified two contrasting demes of A. thaliana with differential tolerance to moderate soil alkalinity: the sensitive deme T6 (c−) and the tolerant A1 (c+) . The better performance of A1 (c+) under iron deficiency conditions was mainly attributed to enhanced root release of coumarin-type phenolics [ 23 ]. However, there is increasing evidence for both quick shoot responses and shoot to root signaling under iron deficiency or bicarbonate stress [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins seem to play a crucial role for Fe acquisition in A. thaliana under high pH conditions [137,157,158]. Differential adaptation to calcareous soils in this species is related to enhanced coumarin exudation [159]. Coumarins are synthesized using precursors from the phenylpropanoid pathway.…”
Section: Polyvalent Elements With a Stable +3-oxidation State: Iromentioning
confidence: 99%